Investigation of the Effect of Process Parameters and Geometry-Related Variations on Residual Stress for Aluminum 7050 Alloy Produced via Laser Powder Bed Fusion - Coskun, Mert; Sagbas, Binnur; Akyildiz, Yagiz; Odabas, Omuer Can (SPRINGER, 2024)
Laser powder bed fusion (L-PBF), one of the additive manufacturing methods, has gained an important place in several fields like aviation, space biomedical, etc., due to its advantages, such as producing complex shaped parts with high quality in shorter times. On the contrary, disadvantages such as high surface roughness, low dimensional accuracy, problems in reproducibility, and residual stress may induce difficulties during the production of the part or usage of the final product. To reduce the residual stress on the parts manufactured by the L-PBF technique, methods such as optimizing geometry-related variations and printing process parameters or applying post-processes can be implemented. This study applied different process parameters and geometry-related variations to investigate the residual stress for aluminum 7050-RAM2 (2% ceramic added) alloy prepared by L-PBF. Laser power, scanning speed, re-melting (double scan) as the process parameters and dimensional variations of the sample (surface area), and different print orientations (0 degrees, 45 degrees) as the geometry-related variations were examined. Minor differences in the process parameters and geometry-related variations affected the residual stress significantly. Especially up-skin scan parameters, build orientation, and size of the top surface area may entirely change the residual stress characteristics.
Keywords: geometry-related variations; laser powder bed fusion; microstructure; process parameters; residual stress; HEAT-TREATMENT; FORMATION MECHANISMS; SURFACE-ROUGHNESS; FLOW; DIFFRACTION; EVOLUTION; POROSITY; QUALITY; Materials Science